1998
DOI: 10.1007/s004030050280
|View full text |Cite
|
Sign up to set email alerts
|

The morphologic changes in lamellar bodies and intercorneocyte lipids after tape stripping and occlusion with a water vapor-impermeable membrane

Abstract: It has been reported that artificial restoration of barrier function by a water vapor-impermeable membrane after tape stripping induces barrier abrogation in hairless mice, impeding rather than enhancing barrier recovery. To address this issue, we examined the morphologic changes in the epidermis after tape stripping and occlusion with a water vapor-impermeable membrane in murine skin. Male hairless mice were used for all studies of barrier perturbation and occlusion. Barrier disruption was achieved by repeate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…Occlusion in general has been known to delay barrier recovery (27)(28)(29)(30). Hence, when clubbed with microneedle technology, it can result in a prolonged therapeutic window.…”
Section: Resultsmentioning
confidence: 99%
“…Occlusion in general has been known to delay barrier recovery (27)(28)(29)(30). Hence, when clubbed with microneedle technology, it can result in a prolonged therapeutic window.…”
Section: Resultsmentioning
confidence: 99%
“…UVB radiation is known to damage the permeability barrier and to enhance percutaneous absorption [12][13][14], Haratake et al [12] demonstrated that the barrier alteration induced by UVB in hairless mice is both dose-and time-dependent, with a lagtime of over 48 h. This delay in the development of the barrier abnormality indicates that the UVB radiation-induced barrier abnormality displays important inherent differences from other models of barrier abrogation. Organic solvents, surfactants, and tape stripping cause an immediate barrier defect due to removal of extracellular lipids from the stratum corneum [19,20], but rather depends upon cellular or metabolic changes in underlying Changes of stratum corneum induced by UVB 33 skin layers that induce a pathogenic cascade that leads eventually to barrier disruption [12].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, even though pores remain open for a period of time, they might not have the same initial dimensions (depth and width), which may affect drug delivery of certain drug molecules. It has been reported that occlusion of disrupted barrier artificially restores barrier function but inhibits barrier recovery (32). Therefore, calcein imaging was also performed for a more direct visualization of pore closure when subjected to the different test conditions.…”
Section: Discussionmentioning
confidence: 99%